Toward the deming prize : the case of Tata Steel (A) - Laha, Arnab Kumar, (SAGE Knowledge. Cases., 2017)
The case series deals with the successful initiation of Tata Steel in various fields. This resulted in Tata Steel becoming lowest cost steel producer in the world. The case series documents the various initiations.